Provision of Pharmaceutical Care Services by Community and Hospital Pharmacists in Oyo State, Nigeria (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Pharmacy practice has evolved as a caring profession and the focus of that caring has shifted from the drug product to the patient. Albeit, patients’ expectations of standard of care are premised on effective and affordable medication.Objectives: This study assesses the adoption of services based on pharmaceutical care concept by community and hospital pharmacists.Methods: A cross sectional study among registered hospital and community pharmacists in Oyo State was conducted for twelve consecutively weeks. Data were obtained using pretested and validated questionnaire. A total of 96 pharmacists participated in the research using Israel (1992) sample size formular. Socio-demographic information of participants and other information related to core pharmaceutical care services were obtained. Descriptive statistics was used to summarize data obtained while test of association between categorical and ranked variables was analyzed by Chi- square and Man-Whitney U tests, respectively, at p